The Analysis of Connotative Meaning in Political Speeches of President Donald Trump - Suardana, Putu; Kaka, Paulina; Isu, Emi (UIBU, 2026)
Political language typically operates beyond its basic or literal meanings. It often uses emotionally appealing and symbolically rich expressions designed to shape public views and influence attitudes. During his time as president, Donald Trump consistently applied these rhetorical techniques. His speeches illustrate how particular words and phrases, filled with underlying implications, can shape audience perception and support ideological stances. This study investigates how Trump’s word choices in public speeches contribute to persuasive political messaging, especially in building group identity and directing public emotion. Employing a qualitative descriptive design, the research examined five purposively chosen speeches to identify the use of connotation and rhetorical elements. The findings reveal that Trump frequently relied on emotionally loaded terms such as “fake news,” “enemy of the people,” and “make America great again” to spark national pride, encourage division, and challenge his adversaries. These findings align with Leech’s theory from 1974, which emphasizes that words possess additional emotional and cultural meanings beyond their dictionary definitions. These layers of meaning increase the persuasive strength of political language. In conclusion, this research contributes to a deeper understanding of how meaning functions in political discourse and emphasizes the role of Semantics in communication studies.